Respons Pertumbuhan dan Produksi Tanaman Jagung (Zea Mays ssp. mays) akibat Aplikasi Dosis Pupuk Kalium dan Nitrogen pada Tanah Kering Masam dengan Pemberian Amelioran - Rochman, Fajar; Priyadi, Priyadi; Rahmadi, Rizky (Universitas Musamus, Merauke, Papua, 2023)
The prospect of increasing productivity of drylands as a food provider is very promising, especially for maize production, which plays an equally important role as a food crop compared to rice. However, in general, the quality of drylands in Indonesia is relatively low. This study aims to further investigate the application of dolomite combined with inorganic fertilizers such as rock phosphate, K and N fertilizers to improve the quality of dry soil, which has the potential to increase maize productivity. The research was conducted at the Seasonal Crop Field of Lampung State Polytechnic from October to December 2022. The study used an experimental method with a Completely Randomized Block Design (CRBD) with 6 treatments and 6 replications. The treatments tested included: k0: without fertilizer; k1: KCl fertilizer dose of 50 kg/ha; k2: KCl fertilizer dose of 100 kg/ha; k3: KCl fertilizer dose of 150 kg/ha; n1: Urea fertilizer dose of 200 kg/ha; n2: Urea fertilizer dose of 250 kg/ha. The results of the study showed that the treatment of KCl fertilizer dose of 100 kg/ha significantly showed the best response on the average parameter of Wet Grain Weight per Cob, Dry Grain Weight per Cob, and Weight per Cob Without Corn Husk of Corn Plants